2017
DOI: 10.1177/0308022617713699
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the factors that influence social and community participation as perceived by people with non-traumatic spinal cord injury

Abstract: Introduction: The number of people with non-traumatic spinal cord injury is rising in developed countries such as Australia and Great Britain. People with non-traumatic spinal cord have different gender, injury and age-related profiles compared to those with traumatically acquired spinal cord injury; therefore, their lived experience is likely to be different. However, the specific issues and challenges that this group faces have not been well investigated. Method: Semi-structured in-depth interviews were cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(46 citation statements)
references
References 29 publications
(43 reference statements)
2
42
0
2
Order By: Relevance
“…Poveča se tveganje za nastanek sekundarnih zapletov, kot so srčno-žilne bolezni, debelost in diabetes tipa 2 (Vissers idr., 2008). Zaradi manjše socialne vključenosti pa se posameznik pogosto sooča z osamljenostjo in depresijo, kar vodi v slabše psihično stanje in nižjo kakovost življenja (Barclay idr., 2017). K temu pripomore tudi spremenjeno doživljanje samega sebe in smisla življenja.…”
Section: Uvodunclassified
“…Poveča se tveganje za nastanek sekundarnih zapletov, kot so srčno-žilne bolezni, debelost in diabetes tipa 2 (Vissers idr., 2008). Zaradi manjše socialne vključenosti pa se posameznik pogosto sooča z osamljenostjo in depresijo, kar vodi v slabše psihično stanje in nižjo kakovost življenja (Barclay idr., 2017). K temu pripomore tudi spremenjeno doživljanje samega sebe in smisla življenja.…”
Section: Uvodunclassified
“…The findings presented here are from a larger study that explored the experience and meaning of social and community participation of people with TSCI and NTSCI. Other parts of this study have been reported elsewhere (Barclay, McDonald, Lentin & Bourke‐Taylor, ; Barclay et al ., ). The aim for this part of the study was to explore the experience of returning to social and community participation following NTSCI.…”
Section: Introductionmentioning
confidence: 97%
“…Maximising people's social and community participation following an acquired disability is an important role of occupational therapists (Roley et al ., ). However, Barclay, Lentin, McDonald and Bourke‐Taylor () identified that there are few studies that have explored the return to social and community participation following non‐traumatic spinal cord injury (Barclay et al .). Non‐traumatic spinal cord injury (NTSCI) is defined as damage to the spinal cord due to pathology such as spinal cord myelopathy, infection or transverse myelitis (Guilcher, Parsons, Craven, Jaglal & Verrier, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, greater perceived environmental barriers (e.g., design of home/community, support at home/community, and transportation) were associated with lower social participation [25][26][27][28]. In a series of qualitative studies, social participation was shown to be impacted by physical and mental health [26][27][28][29], societal attitudes [26][27][28][29], and changes in social networks [26,27]. These factors have also been shown to influence return to work, which is an important marker of a sense of belonging [30].…”
Section: Introductionmentioning
confidence: 99%